Empathy Training for Reducing Bullying Behavior among Adolescents: A Scoping Review - Hikmat, Rohman; Yosep, Iyus; Hernawaty, Taty; Suryani, Suryani; Mardhiyah, Ai; Widianti, Efri; Maulana, Indra; Rafiyah, Imas; Sutini, Titin; Sriati, Aat (Poltekkes Kemenkes Semarang, 2025)
Background: Bullying is a serious problem in adolescents. The negative impact of bullying is the occurrence of physical and psychological problems in adolescents. These problems can be prolonged and lead to criminal behavior in adolescents. Empathy is one of the aspects that influence bullying behavior.Purpose: to describe empathy training in reducing bullying behavior in adolescents.Method: This research design used a scoping review. Searching strategy used PRISMA Extension for Scoping Review with major keywords are empathy training, bullying, and adolescents. The databases used were CINAHL, PubMed, and google scholar. The inclusion criteria used were original research, quasi experiment design, publication period of the last 10 years (2012-2022), and using English. Data analysis used a descriptive approach.Results and Discussion: The authors found 5 articles that discuss empathy therapy in reducing bullying behavior significantly (p value <0.05). Empathy therapy is carried out with discussion activities, role playing, counseling, and using empathy therapy modules. This intervention is carried out by involving the teacher as a companion during the intervention process.Conclusion: Empathy therapy needs to be given to the perpetrator or victim so that repeated bullying behavior does not occur in adolescents. So that empathy therapy can be a reference for schools and health workers in preventing bullying in students at school.